Czy sprzęt którym posługujesz się nieda się ulepszyć? (Gdańsk : [s.n.], 1953)
Plakat propagandowy.
Tytuł tak jak na plakacie "nieda".
Keywords: Propaganda -- Polska -- 1945-1970 -- druki ulotne; Plakaty -- Polska -- 1945-1970.